Comparación de intervalos de confianza para el coeficiente de correlación (2013)
The construction of conﬁdence intervals to estimate the correlation in the normal bivariate and multivariate distribution, ρ, is an important problem in applied statistical work. One of the main purposes of this work is to make a review of the diﬀerent procedures for their construction. In addition, a simulation study was conducted to analyze the behavior of real conﬁdence levels and compare them to theoretical ones, analyze the behavior of the lengths of the conﬁdence intervals achieved by the nine methods considered and determine which methodology provides the shortest intervals. Likewise an indicator that summarizes more eﬀectively the quality of the analyzed interval was also obtained.